PENGARUH INTELLECTUAL CAPITAL TERHADAP FINACIAL PERFORMANCE PADA PERUSAHAAN JASA YANG TERGABUNG DALAM LQ45 - B4110041, MEGA ASTININGSIH (Jurnal KIAFE, 2014)
Lately, the company began to use the Intellectual Capital (IC) as an asset in improving financial performance, is due to the emergence of corporate awareness that IC is a platform for firms to be more competitive than other companies. The purpose of this study is to empirically examine the effect of IC on the financial performance of the company. Intellectual Capital (IC) is an independent variable and financial performance as the dependent variable. The sample in this study based on purposive sampling. The data used is a data services company incorporated in LQ45, with the audited financial statements from the year 2010 until the year 2013 data are calculated using the model Pulic, the Intellectual Capital Value added coefficient (VAICTM) for Intellectual Capital (IC) and Return on Assets (ROA), Earning per share (EPS) for the company's financial performance. Key words: financial performance, Intellectual Capital (IC), the Intellectual Capital Value added coefficient (VAICTM).